EFFECTIVE PUBLIC TRANSPORT SYSTEM USING THE CONCEPT OF FUZZY SPANNING TREE - Priyaa, Mohanapriyaa (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
Â A network is a nodes joined by a set of arcs much like a highway system linking major cities. The concept of simple variation of maximal flow problem, fuzzy edge cut set, arcs and vertex capacities, multiple sources and settles of fuzzy graphs are consulted. The fuzzy vertex condensation of flow, a maximum flow matrix by a spanning tree using examples are analyzed. This paper highlights with examples for the changes effects in the provisioning of public bus transport services to make them more efficient and effective.